Sistem Informasi Penanggulangan Kemiskinan Terpadu Menggunakan Model SIG ( Studi kasus : BAPPEDA Landak) - Agung Sasongko (Universitas Bina Sarana Informatika, 2017)
ABSTRACTThis paper discusses the design of Geographic Information System to facilitate the reading of Social Protection Program Data Collection (PPLS) in 2015 at the respective areas of Village and District in Landak District. In general, the availability of information on PPLS data in an area comes from the National Team for Accelerating Poverty Reduction (TNP2K). In order for the work plan at the Regional Work Unit (SKPD) in Landak District to have a structured and synergized direction for the acceleration of poverty reduction, it is necessary to distribute information in the form of data of poverty indicators that can be accessed by each SKPD. So direction of policy of work plan is not mutual Overlap, but complement each work plan between each SKPD.Visualisation data in the form of infographic in order to facilitate the reading of the data. The system is designed to be web-based for multiuser access, ie for all SKPD within the district government of Landak. The research method used in the design of qualitative descriptive analysis, while the method of software development using Software Development Life Cycle with Waterfall model.Keywords: Poverty allevation, geographic information system.